Paramosina, a new genus of high Andean Limosininae (Diptera: Sphaeroceridae) - Marshall, Stephen A.; Yau, Tiffany (Zootaxa, 2014)
Paramosina, a new genus of Sphaeroceridae, is described on the basis of one abundant new species, Paramosina hirsuta Marshall, from the Ecuadorian Andes.